2022
DOI: 10.22541/au.166723085.56550911/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grazing by semi-feral cattle and horses supports plant species richness and uniqueness in grasslands

Abstract: Question: How do naturalistic grazing in contrast to mowing and free succession affect plant community composition and species richness in a temperate grassland grazed by semi-feral cattle and horses? Location: Mols Laboratory, DenmarkMethods: We investigated grazing exclosures in the rewilding area of the Mols Laboratory, four years after its establishment. We focused on moist to dry grassland vegetation, i.e. excluding scrub and woodland. Each experimental block consisted of five 5 × 9 m plots, representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Multiple studies have shown positive effects of year-round grazing with these species on plant diversity and vegetation structure (e.g., Gilhaus et al, 2014;Köhler et al, 2016). In the Mols Laboratory in Denmark, where our study was conducted, exclosure experiments have shown higher plant species richness, indications of higher floristic uniqueness, and higher forbs-to-graminoids ratios in plots with year-round or winter grazing compared to mowing or summer grazing (Bonavent et al, 2022). These studies highlight the importance of natural grazing regimes for plant species diversity.…”
Section: Introductionmentioning
confidence: 72%
“…Multiple studies have shown positive effects of year-round grazing with these species on plant diversity and vegetation structure (e.g., Gilhaus et al, 2014;Köhler et al, 2016). In the Mols Laboratory in Denmark, where our study was conducted, exclosure experiments have shown higher plant species richness, indications of higher floristic uniqueness, and higher forbs-to-graminoids ratios in plots with year-round or winter grazing compared to mowing or summer grazing (Bonavent et al, 2022). These studies highlight the importance of natural grazing regimes for plant species diversity.…”
Section: Introductionmentioning
confidence: 72%